Effect of surfactant modified clinoptilolite added propagating substrate in the growth of clinancathus nutans - Dzkulfli, Noor Hidayah (2014)
Nitrogen (N), phosphorus (P) and potassium (K) nutrients are important for plant growth especially for herbal plants. N is essential for leaf growth, P is crucial for rooting development of the plants while K is important for fruit and flower development of plants. Zeolite (clinoptilolite) cannot adsorb anions such as phosphate (PO43-) and nitrate (NO3-) which vital for the plant growth because of its negative charge. Hence, an experiment was carried out to modify clinoptilolite with cationic surfactant, hexadecyltrimethylammonium-bromide (HDTMA-Br) producing surfactant modified clinoptilolite (SMC) which later then added to propagating substrate to form controlled release propagating substrate (CRPS) which can hold and control the anion and cation release. The release behaviour of PO43-, NO3- and K? from CRPS was studied for ten days. Results showed that, the combination of SMC with 50 g propagating substrate could control the anions and cation release and furthermore enhance the growth of Clinacanthus nutans during sowing time. Therefore, SMC is needed to be added in propagating substrate to control the release of nutrients during germination or sowing time.